Identity Preservation in International Feed Supply Chains. (April 2016) - Varacca, Alessandro; Soregaroli, Claudio
Summary: With the progressive internationalisation of food and feed supply chains, Identity Preservation (IP) has become an important feature for traded agricultural products to ensure that the right product reaches the right customer. In this article, we focus on IP based on voluntary technical schemes for non‐Genetically Modified (non‐GM) crops. Three critical steps are identified along the supply chain: product management at the origination/destination port, product transportation and product processing in dedicated plants. Best management practices and coordination mechanisms are implemented by actors along the supply chain to ensure that the product maintains its IP. This translates into a higher degree of dependency among actors. Although ' formal ' vertical integration through mergers and/or acquisition is rare, voluntary schemes require very tight coordination which is enforced through downstream‐driven technical requirements and process certification standards. Market uncertainty is also observed, as the future availability of non‐GM crops could become scarce, raising input prices for downstream firms. Food processors and retailers that invested in the non‐GM attribute as part of their brand equity are those at higher risk. For these players it is crucial to assure product availability in the long run and to make sure consumers are willing to pay the extra costs of IP goods. Abstract : With the progressive internationalisation of food and feed supply chains, Identity Preservation (IP) has become an important feature for traded agricultural products to ensure that the right product reaches the right customer. In this article, we focus on IP based on voluntary technical schemes for non‐Genetically Modified (non‐GM) crops. Three critical steps are identified along the supply chain: product management at the origination/destination port, product transportation and product processing in dedicated plants.